Social Media Marketing and Its Influence on Brand Equity: The Mediating Role of Word of Mouth and E-Word of Mouth - Dhewi, Titis Shinta; Kurnianto, Mickhael (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2023)
The purpose of this study is to examine the nexus between social media marketing and brand equity, and the role of word of mouth and electronic in mediating this connectivity word of mouth. A quantitative approach with a descriptive explanatory design is employed to estimate the link between the variables observed. The study adopts purposive sampling technique with a sample size of 200 participants, and data is analyzed using Path Analysis with Warp-PLS 3.0. The findings indicate that social media marketing positively influences brand equity, and both word of mouth and e-word of mouth play a vital role in escalating brand equity. The study also confirms the mediating role of word of mouth and e-word of mouth in explaining the connectivity between social media marketing and brand equity. The results suggest that the assimilation and educational-based tourism management can promote tourism through social media to enhance the value of tourist attractions’ names, encouraging the public to enlarge in word-of-mouth promotion.